Resveratrol Ameliorates the Components of Hepatic Inflammation and Apoptosis in a Rat Model of Streptozotocin‐Induced Diabetes. Issue 1 (7th January 2016) - Pektaş, Mehmet Bilgehan; Sadi, Gökhan; Koca, Halit Bugra; Yuksel, Yasemin; Vurmaz, Ayhan; Koca, Tulay; Tosun, Murat
ABSTRACT: Preclinical Research Trans‐resveratrol has a wide range of biological effects that reflect its antioxidant, anti‐inflammatory, anticarcinogenic and cardioprotective properties. This study was conducted to elucidate the potential role of resveratrol on hepatic inflammation and the apoptotic pathway components Bcl‐2, Bax and p53 in a streptozotocin (STZ)‐induced rat model of diabetes mellitus. Inflammatory and apoptotic biomarkers indicated a reduction in hepatic erythropoietin (1.26‐fold) and increased asymmetric dimethylarginine (3.9‐fold), visfatin (1.6‐fold), inflammatory interleukins and TNF–α contents (approximately twofold each) in the diabetic animals. Induction of inducible nitric oxide synthase gene (2.04‐fold) and protein expression (1.24‐fold) was also observed. Immunohistochemical studies showed enhancement of the apoptotic biomarkers Bax and p53 in diabetic animals. STZ‐induced diabetic male Wistar rats were treated with resveratrol (20 mg/kg/day i.p.). Resveratrol succeeded to recover most of these inflammatory and apoptotic elements. Therefore, inflammatory and apoptotic pathways were proved to be affected by STZ‐induced diabetes in several aspects and resveratrol might contribute hepatoprotective effects as evidenced from this study. Drug Dev Res 77 : 12–19, 2016. © 2016 Wiley Periodicals, Inc.